PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT. Sianyu Perkasa Semarang) - Winda Listiyana; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2019)
Quality human resources is one of the key factors for business success. Based on the data obtained, the performance of employees at PT. Sianyu Perkasa Semarang had a decrease in its business, especially in the annual sales department and the attendance of its employees. From these problems, it appears to be related to increasing employee work discipline related to work motivation and the work satisfaction. Related, decreased work discipline ultimately increases the decline in employee performance. This study aims to determine the influence of work motivation and job satisfaction on employee performance through work discipline as an intervening variable. The type of research is explanatory research. The sample used were 72 respondents who are employees at PT. Sianyu Perkasa Semarang. The datas are collected by questionnaire with a Likert measurement scale. The results of this study show that: (1) there is a significant effect of motivation on the work discipline of PT. Sianyu Perkasa with a calculated T value  4,258> T table 1,293; (2) there is a significant effect of job satisfaction on the work discipline of PT. Sianyu Perkasa with T count 6.201> T table 1,293; (3) there is a significant effect of work motivation and job satisfaction on the work discipline of PT. Sianyu Perkasa with F count  22.126> F table 2.72; (4) there is an effect of work motivation on the employees performance of PT. Sianyu Perkasa with T count 6.195> T table 1,293; (5) there is a significant effect of job satisfaction on employee performance with a calculated T value 7.646> T table 1,293; (6) there is a significant effect of work discipline on the employees performance with calculated T value  7.133> T table 1,293; (7) the influence of work motivation, job satisfaction and work discipline on employee performance with F count 35.208> F table 2.38; (8) based on the work motivation sobel test that affects employee performance through work discipline, has a calculated T value (3.27554686)> T table (1.99444); (9) job satisfaction that affects employee performance through work discipline, has T count (3.275039761)> T table (1.99444).